2015
DOI: 10.1785/0120140241
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Simulation of Strong‐Motion Records from the 2012 Ahar–Varzaghan Dual Earthquakes, Northwest of Iran

Abstract: Here, the generalized inversion of S-wave amplitude spectra is employed for deriving the site response and S-wave attenuation (quality factor) in the northwest region of Iran. A total of 279 strong-motion accelerograms recorded at distances below 200 km from 41 earthquakes with moment magnitudes ranging from M w 3.8 to 6.5 are used to determine the region-specific attenuation model. The site responses have been determined for all 54 stations individually. The bulk of strong-motion data (i.e., 184 records) come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Anomaly trend correlates with the major source of seismicity in Ahar-Varzaghan and, mainly, the fault mechanism with an E-W, parallel to the coastline. Results of ground motion simulation [53] also conrm that the causative fault of this earthquake has an E-W trend. Conformity of anomaly zone with the fault rupture area also supports the validity of the statistical analyses.…”
Section: Discussionmentioning
confidence: 53%
“…Anomaly trend correlates with the major source of seismicity in Ahar-Varzaghan and, mainly, the fault mechanism with an E-W, parallel to the coastline. Results of ground motion simulation [53] also conrm that the causative fault of this earthquake has an E-W trend. Conformity of anomaly zone with the fault rupture area also supports the validity of the statistical analyses.…”
Section: Discussionmentioning
confidence: 53%
“…In the NW Iran, however, much less work has been conducted. Among of those, Zafarani et al (2015) found the frequency-dependent S-wave quality factor, Qs =99 f 0.77 , from the stochastic simulation of strong-motion records of the Ahar-Varzaghan earthquakes.…”
Section: Ijge 2017 3(3): 73-84mentioning
confidence: 99%
“…We use the density of medium as 2.8 g/cm 3 and shear wave velocity as 3.5 km/s (Zafarani et al 2015), respectively. The fault plane solution for each event used in the present work could not be determined owing to the small number of recording stations.…”
Section: Inversionmentioning
confidence: 99%
“…Z. Sun et al., 2018; Sutar et al., 2020; Tanırcan & Yelkenci‐Necmioğlu, 2020; Toni, 2017; Zafarani et al., 2015). Considering the EXSIM approach, this study simulated the Jiashi earthquake that occurred in Xinjiang on 19 January 2020.…”
Section: Introductionmentioning
confidence: 99%